Effects of lorcaserin on pre‐existing valvulopathy: A pooled analysis of phase 3 trials. Issue 1 (26th November 2016) - Weissman, Neil J.; Smith, Steven R.; Fain, Randi; Hall, Nancy; Shanahan, William R.
Abstract : Objective: To evaluate the effects of lorcaserin in patients with pre‐existing Food and Drug Administration (FDA)‐defined valvulopathy. Methods: This is a pooled, post hoc analysis of three Phase 3 studies. BLOOM and BLOSSOM patients were 18 to 65 years of age without diabetes and with a body mass index (BMI) of 27 to 29.9 kg/m 2 and ≥1 weight‐ related comorbidity or a BMI of 30 to 45 kg/m 2 . BLOOM‐DM patients had a BMI of 27 to 45 kg/m 2 and type 2 diabetes. Patients were treated with placebo, lorcaserin 10 mg once daily, or lorcaserin 10 mg twice daily. Serial echocardiographs were obtained at baseline and every 6 months. Results: Included patients ( N = 169) had FDA‐defined valvulopathy at baseline and a week 52 echocardiogram. At week 52, 35.5% and 52.7% of patients experienced changes from baseline in aortic and mitral regurgitation, respectively. Numerically greater proportions of patients taking lorcaserin versus placebo had decreases in aortic (33.0% vs. 28.3%) or mitral (41.3% vs. 36.7%) regurgitation. Fewer patients taking lorcaserin versus placebo had increases in aortic (2.8% vs. 6.7%) or mitral (8.3% vs. 21.7%) regurgitation. No adverse event‐related discontinuation was due to a valve problem. Conclusions: These data suggest that lorcaserin does not adversely affect valvular disease in patients with pre‐existing FDA‐defined valvulopathy.